Very rare angioleiomyoma of the male urethra - Pacík, D; Dolezel, J; Skoumal, R; Bucek, J; Kladenský, J (International urology and nephrology, 1993)
Herein is reported a case of angioleiomyoma, i.e. a benign tumour arising predominantly from smooth muscle cells of the vessel wall, in a yet unreported locality, the urethra. The closest to the tumour presented by us are leiomyomas of the urethra, so far described only in females. The angioleiomyoma of our case manifested itself as a stricture of the male urethra and resection operation showed to be the best approach with elimination of the patient's complaints.
Keywords: Middle Aged; uretra; mužské pohlaví; nádory močové trubice; radiografie; Humans; angiomyom; Angiomyoma; Urethra; Urethral Neoplasms; lidé; Male; Radiography; lidé středního věku